Geomorphology of the island of Tinos - ΛΕΙΒΑΔΊΤΗΣ, Γ.; ΑΛΕΞΟΥΛΗ-ΛΕΙΒΑΔΙΤΗ, Α. (Bulletin of the Geological Society of Greece, 2001)
Morphology of Tinos Island is controlled mainly by lithology and tectonics. A significant factor is also the climate; the very high humidity and the strong winds of NNE directions. These special climate characteristics cause intense chemical alteration and cellular weathering at schists and granodiorites. The relief is fairly mountainous. Mt. Tsiknias in the south is the highest mountain (725m). In the central part of the island there are Mesovouni (647m) and Prasa (614m). The slopes of the valley-sides vary a lot depending mainly on the original dip. The relief is smooth while slopes of 15-45% comprise 73% of the island. Three morphological units with different relief type can be distinguished, that results from lithological differences and the type of erosion. The first unit covers the larger part of the island and consists of mica-schists with marble intercalation. The second unit is observed at the mountains Tsiknias, Vouno and Marias. It consists of green schist, clorittalkschists. It is characterized generally of smooth relief with acute notched peaks and Tafoni. The third unit comprises the area of the plutonic rocks. It is characterized by dispersed rounded bulks of granite and spheroidal weathering. Petrologie examination showed biotitic-monzogranit in the area Steni-Volax and biotitic-granodiorit in Livada. In the spherical bulks of Livada Tafoni are created. The spheroidal weathering is owed to chemical processes. The weathered mantle was identified sericitization. The island is crossed by a watershed, which is parallel to the long axis of the island trending NW-SE, and separates the island in two asymmetric parts. The watershed is coincided to the axis of the folds. Pianation surfaces are observed at 100m, 200m, 300- 350m, 410-430m and at 600m. The topographic slopes along the coasts of Tinos present a wide range of values. The slopes of the coasts of the 500m cross-sectional coastal zone, are higher of those of the 1000m one. Clear relation between the slopes of these zones and the corresponding lithologie formations is not observed. It is believed that the main factors which controls the slope morphology of the coastal zone is the tectonic and the weathering.